COMMUNITY-ACQUIRED PNEUMONIA OLEH KLEBSIELLA PNEUMONIAE DI RSUP DR. M. DJAMIL PADANG TAHUN 2024: GAMBARAN MORTALITAS TINGGI DAN TANTANGAN KLINIS - Ruhsyahadati Ruhsyahadati; Nana Liana; Rahma Triyana; Dian Puspita; Muhammad Rizki Saputra; Roland Helmizar; Rifkind Malik; Aulia Akbar (Yayasan Nusantara Hasana Berdikari, 2026)
Community-acquired pneumonia (CAP) caused by Klebsiella pneumoniae is frequently associated with severe clinical courses and high mortality, particularly among elderly patients and those with comorbidities. The increasing rate of antimicrobial resistance has further limited the effectiveness of standard empirical therapy. This was a retrospective descriptive observational study using secondary data from medical records of hospitalized CAP patients at Dr. M. Djamil General Hospital, Padang, from January 2022 to December 2023. Subjects were adults (≥18 years) diagnosed with CAP and with positive cultures for K. pneumoniae. Variables included demographic characteristics, length of hospital stay, clinical outcomes, and antibiotic susceptibility patterns. Data were analyzed using univariate descriptive analysis. A total of 50 patients were included, predominantly male (58%) and aged over 65 years (40%). The most frequent comorbidities were hypertension (60%) and diabetes mellitus (36%). The mean length of hospital stay was 14 days. Mortality was high, reaching 56%. Antibiotic susceptibility testing showed the highest sensitivity to meropenem (96%) and amikacin (92%), while commonly used first-line agents such as ceftriaxone, ampicillin–sulbactam, and ciprofloxacin demonstrated low sensitivity (<15%). CAP due to Klebsiella pneumoniae at Dr. M. Djamil General Hospital is associated with very high mortality and widespread resistance to first-line antibiotics. Empirical therapy should be guided by local antibiogram data and supported by strong antimicrobial stewardship programs.